The Potential of Mangrove Stem Extract (Aegiceras corniculatum) on the Haematocrit Value - Gustiadi Saputra; Theresia Indah Budhy; Muji Rahayu; Budi Santosa (Universitas Airlangga, 2022)
Hematocrit examination is an examination used to measure the concentration of red blood cells (erythrocytes) in the blood stated in percent (%). The usual hematocrit examination uses the anticoagulant EDTA, is expensive, and rarely distributed in remote area. Alternative anticoagulants are currently being studied, one of which is the extract of mangrove stems (Aegiceras corniculatum). This study aims to determine the difference in hematocrit values ​​using the anticoagulant EDTA and extract of mangrove stems (Aegiceras corniculatum). The type of this research was analytic observational with a cross-sectional research design. Samples were taken by non-random purposive sampling of 16 female students from a total of 31 students of class D semester VIII of Health Analyst Universitas Muhammadiyah Semarang. The results showed average hematocrit value using EDTA anticoagulant was 42.38% by using the microhematocrit method. Meanwhile, the average hematocrit value using mangrove stem extract (Aegiceras corniculatum) is 20.88%. The hematocrit examination using the EDTA anticoagulant were higher than using the extract of mangrove stems (Aegiceras corniculatum). It showed a value of 0.000 with a significant level of 0.05, which is 0.000 <0.05. Therefore, there is a difference in hematocrit value using EDTA anticoagulant and mangrove stem extract (Aegiceras corniculatum).